Transcriptome profiling explores the immune defence mechanism of triploid Pacific oyster (Crassostrea gigas) blood against Vibrio alginolyticus based on protein interaction networks. (June 2023) - Zhang, Enshuo; Li, Zan; Lv, Tingjin; Fu, Jingjing; Dong, Luyao; Feng, Yanwei; Sun, Guohua; Xu, Xiaohui; Cui, Cuiju; Wang, Weijun; Yang, Jianmin
Abstract: Triploid oysters have provided the oyster industry with many benefits, such as fast growth rates, meat quality improvement, and increased oyster production and economic benefits, since the first report on triploid oysters was published. The development of polyploid technology has remarkably increased the output of triploid oysters to meet the increasing demand of consumers for Crassostrea gigas in the past decades. At present, research on triploid oyster has mainly focused on breeding and growth, but studies on the immunity of triploid oysters are limited. According to recent reports, Vibrio alginolyticus is a highly virulent strain that can cause disease and death in shellfish, shrimp, as well as serious economic losses. V. alginolyticus may be a reason why oysters die during summer. Therefore, using V. alginolyticus to explore the resistance and immune defense mechanisms of triploid oysters against pathogens presents practical significance. Transcriptome analysis of gene expression was performed in triploid C . gigas at 12 and 48 h after infection with V. alginolyticus, and the respective 2257 and 191 differentially expressed genes (DEGs) were identified. The results of GO and KEGG enrichment analyses showed that multiple significantly enriched GO terms and KEGG signaling pathways are associated with immunity. A protein–protein interaction network was constructed to investigate the interaction relationship of immune-related genes. Finally, we verified the expression situation of 16 key genes using quantitative RT-PCR. This study is the first to use the PPI network in exploring the immune defense mechanism of triploid C. gigas blood to fill the gap in the immune mechanism of triploid oysters and other mollusks, and provide valuable reference for future triploid farming and pathogen prevention and control. Highlights: This study is the first transcriptome analysis based on protein interaction network in triploid Crassostrea gigas. It provides valuable gene resources for further study of the immune responses in invertebrate blood. The data serve as a foundation for further research on invertebrates against to pathogen.